Regimes with the dynamic chaos in analisis of linear systems - Antipov, V.S.; Buts, V.A. (Вопросы атомной науки и техники, 2014)
The examples are shown which demonstrate that in the course of analysis of linear systems the modes with dynamic chaos can occur. This can happen when for analysis of linear systems the change of variables is used resulting in the need to investigate either non-linear equations or non-linear functions. In the plasma physics field such situation may arise, e.g., when diagnosing some plasma parameters. Приведены примеры, которые показывают, что при анализе динамики линейных систем могут возникать режимы с динамическим хаосом. Это случается, когда для анализа линейных систем используются замены переменных, которые приводят к необходимости исследовать либо нелинейные уравнения, либо нелинейные функции. Для физики плазмы такая ситуация может возникнуть, например, при диагностике параметров плазмы. Наведено приклади, які показують, що при аналізі динаміки лінійних систем можуть виникати режими з динамічним хаосом. Це трапляється, коли для аналізу лінійних систем використовуються заміни змінних, які призводять до необхідності досліджувати, або нелінійні рівняння, або нелінійні функції. Для фізики плазми така ситуація може виникнути, наприклад, при діагностиці параметрів плазми.